MANAJEMEN PROYEK SISTEM INFORMASI PENGGAJIAN KARYAWAN PADA PT MOJOPAHIT MANDIRI JAYA SENTOSA - Anindita Kastarini; Edhi Prayitno (Journal of Innovation And Future Technology, 2025)
In the era of globalization and rapid technological advancement, the need for computerized information systems has become essential for improving operational efficiency within companies. PT Mojopahit Mandiri Jaya Sentosa, a sales-oriented company based in Tangerang City, currently manages its payroll processes manually—including attendance tracking, salary calculations, and report generation. This manual approach often leads to data entry errors, delays in information retrieval, and inaccurate administrative reports. This study aims to design and develop a computerized payroll information system to address these challenges. The project development process is guided by the Project Management Body of Knowledge (PMBOK® Guide) framework, which comprises five key phases: initiation, planning, execution, monitoring and controlling, and closing. By implementing the PMBOK methodology, the system development is carried out in a structured and measurable manner to ensure that the final product meets user needs, improves payroll accuracy, and streamlines administrative workflows. The resulting system is expected to provide the Administration Division and Accounting Manager with a more efficient, accurate, and transparent tool for managing employee data and payroll processes, ultimately enhancing the quality of the company’s financial reporting.